Clinical presentation and endoscopic findings in adult patients with eosinophilic esophagitis: Eosinophilic esophagitis in adults - Türkel Küçükmetin, Nurten; Tiftikçi, Arzu; Baba, Füsun; Solakoglu, Tevfik (Journal of Surgery and Medicine, 2022)
Background/Aim: The frequency of eosinophilic esophagitis has been rising over the last decades. It is diagnosed primarily based on symptoms and endoscopic and histopathological examination findings. Although eosinophilic esophagitis is not associated with malignancy, it remains an important condition affecting both children and adults, as it is associated with morbidity such as dysphagia, food impaction, and esophageal strictures. This study aimed to define clinical and endoscopic characteristics of adult patients diagnosed with eosinophilic esophagitis based on recently recommended histopathological criteria. Methods: This retrospective cross-sectional descriptive study included 54 adult patients (mean age: 33.6 yr, range: 16–61 yr) who underwent upper gastrointestinal system endoscopy for dyspeptic complaints (epigastric pain, reflux, dysphagia, or food impaction) and diagnosed with eosinophilic esophagitis based on the latest histopathological criteria (≥15 eosinophils per high-power field). Patients with a history of malignancy were excluded. Patients’ clinical, endoscopic, and histopathological data were examined. Results: In patients diagnosed with eosinophilic esophagitis, the most common presenting complaint was dysphagia (61.1%), followed by dyspepsia (24.0%), regurgitation (16.6%), chest pain (16.6%), epigastric pain (12.9%), food impaction (11.1%), and halitosis (3.7%), without any age predilection for the complaints. White papules and linear furrow were the most frequent findings on endoscopic examination (35.1% each), followed by circular rings (24.0%), paleness (22.2%), normal endoscopic finding (20.3%), and small-caliber esophagus (11.1%). Conclusion: The diagnosis of eosinophilic esophagitis remains challenging due to considerable variations in definitions and in the relative frequencies of endoscopic findings. Therefore, we recommend combining clinical, endoscopic, and histologic criteria to establish diagnosis. The identification of standards for diagnosis in future studies is warranted.